PROVIDING REGISTRATION SERVICES FOR THE ELDERLY ACCORDING TO THE 4 PRINCIPLES OF THE PERSONNEL SUBDISTRICT ADMINISTRATION ORGANIZATON IN RON PHIBUN DISTRICT NAKHON SI THAMMARAT PROVINCE - Dunkon, Sirorat; Chamnanputtiporn, Supreecha (Journal of MCU Nakhondhat, 2024)
This research aims to 1) Provide registration services for the elderly according to the 4 principles of the personnel and 2) Guidelines regarding the promotion of registration services for the elderly according to the 4 principles of the administrative organization personnel. Subdistrict in Ron Phibun District Nakhon Si Thammarat Province This research is a mixed methods research. Quantitative research Sample group of 384 people. Qualitative research. There were 5 key informants. The statistics used were frequency, percentage, mean and standard deviation. It was found that 1) The provision of registration services for the elderly according to the 4 principles of the Subdistrict Administrative Organization personnel in the area Ron Phibun District Nakhon Si Thammarat Province Overall it was at a high level, with an average value ( = 4.43, S.D. = 0.33). When considering each area, it was found that the area with the highest average was For the principle of morality, the average value ( = 4.46, S.D. = 0.40), followed by the principle of physical conduct, the average value ( = 4.43, S.D. = 0.35), the principle of mentality, the average value ( = 4.42, S.D. = 0.35), and In terms of wisdom principles, the average values ( = 4.41, S.D. = 0.43), respectively. 2) Guidelines for promoting the provision of registration services for the elderly according to the 4 principles of the Subdistrict Administrative Organization personnel in Ron Phibun District. Nakhon Si Thammarat Province includes: 1.1) Principles of the Body of Peace, personnel providing service with heart Listen to the opinions of the elderly. 1.2) Principles of precepts. Personnel work correctly according to the rules and regulations and have ethics in providing services. 1.3) Principles of mentality. Personnel in the principles of mental meditation (mental cultivation, mental development, mental training to be stable and prosper with morality) namely that officials have minds focused on the work they provide and 1.4) Principles of wisdom and meditation Personnel should regularly develop their knowledge about their work and should have the skills to solve specific problems.